ANALISIS TINGKAT KEBERHASILAN INSEMINASI BUATAN PADA SAPI SIMMENTAL DAN SAPI PERANAKAN ONGOLE DI KECAMATAN PURWANEGARA KABUPATEN BANJARNEGARA - Supranoto; Ngudi Santosa; Fani Evadewi; Tri Sukmaningsih; Mulyoto Pangestu (MEDIA PETERNAKAN, 2025)
This study aims to determine the success rate of artificial insemination of Simmental and Ongole crossbreed cattle in Purwanegara and the factors that influence its success. The results of the study of the success rate of artificial insemination showed that the average value of Secvice Per Conception (S/C) Simmental was 1.394 ± 0.125 and Ongole crossbreed was 1.295 ± 0.117 both approaching 1.00 identifying that each Simmental and Ongole crossbreed cow requires 1 dose of artificial insemination before reaching pregnancy and reflects the productivity level of Simmental and Ongole crossbreed cattle. The results of the study showed that the Conception Rate (CR) value in Simmental cattle was 78% and Ongole crossbreed reached 82%, in the Ongole crossbreed cattle conception rate parameter it was slightly higher when compared to Simmental, this shows that the CR of Ongole crossbreed cattle is better than Simmental cattle. The high Non Return Rate (NRR) value is 78%, while the Ongole crossbreed cattle have a higher non return rate of 82% so that the Ongole crossbreed has a higher NRR than Simmental. The success factors of artificial insemination are the fertility rate at high fertility based on the age and BCS condition of the cattle, the efficiency of the inseminator's work, the duration of reporting until artificial insemination and the quality of nutrition, temperature, climate, weather and cattle maintenance management